The Implementation Of Child-Friendly School Policies In Elementary Schools - Pujoko; Astuti, Dwi Hajar Fitri; Nurkolis (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research examines the implementation of the School-Friendly Child (SFC) policy at SD Negeri Sambiroto, a primary school in Rembang, Indonesia. The study aims to evaluate the effectiveness of the SFC policy, focusing on its key components, including child protection, inclusive education, and fostering a positive learning environment. The research employs a qualitative case study approach, using interviews, observations, and document analysis as data collection methods. The findings reveal that while the school has made substantial progress in applying the policy, there are significant challenges regarding resource limitations, teacher preparedness, and resistance to change. The school has tried to engage parents and the local community, which is crucial in ensuring the policy’s success. Key factors for successful implementation include strong leadership, ongoing teacher training, and effective communication among stakeholders. The study also highlights the importance of continuously evaluating and adapting the policy to address emerging challenges. This research provides insights into the practical aspects of implementing child-friendly policies in schools and offers recommendations for improving the quality of education and school management.